General analysis and optimization of a two-stage power management circuit for electrostatic/triboelectric nanogenerators. (1st December 2022) - Zhang, Hemin; Galayko, Dimitri; Basset, Philippe
Abstract: Triboelectric nanogenerators (TENGs) generate high AC voltages that are often rectified using stable charge pumps. This paper provides for the first time a comprehensive general theory that determines the optimal electrical bias conditions for this class of rectifiers. In this work, the proposed generic formulas have been applied to full-wave and half-wave diode bridges. Key figures have been demonstrated like for instance the optimal bias voltage or the maximum converted energy. It is confirmed that half-wave rectifiers always have a higher saturated voltage, as well as higher maximum energy per cycle, but at the cost of longer start-up time. On the contrary, full-wave rectifiers perform better only when the output voltage is much lower than the internal triboelectric voltage of the TENG. These rectifiers followed by a buck DC-DC converter have also been studied in details, often required to provide a low output voltage. We showed that the optimal buck' switch activation is between .5 and .7 of the charge-pump saturation voltage, depending on the hysteresis of the switch, and that the charging time of the output capacitor is at least twice as fast with a half-wave rectifier than with a full-wave rectifier. The theoretical results were confirmed by simulations and experiments using a plasma switch. Graphical abstract: This paper provides a comprehensive general theory that determines the optimal electrical bias conditions for stable charge-pump used as rectifiers, such as for instance the optimal bias voltage, the maximum energy converted, or the number of actuation cycles required to reach these values. We have applied the generic formulas developed in this work to full-wave and half-wave diode bridges. We also studied in details these rectifiers with high-voltage output followed by a buck DC-DC converter, often required to provide a low- voltage output. We showed that the optimal buck' switch activation is between.5 and.7 of the charge-pump saturation voltage depending on the hysteresis of the switch, and that the charging time of the large and low-voltage output capacitor is at least twice as fast with a half-wave rectifier than with a full-wave rectifier. ga1 Highlights: New comprehensive general theory to determine the optimal electrical bias conditions for stable charge pump rectifiers, such as diode bridges. Various key-figures have been derived from the generic formulas to help TENG's designers to optimize their devices. Optimum switch actuation in a Buck DC-DC down-converter for maximum efficiency of a TENG, depending on the switch hysteresis.